#Mypathtolaw: understanding access to the legal profession through a ricoeurian analysis. Issue 3 (3rd July 2022) - Flanagan, Ruth; Mountford-Zimdars, Anna; Channon, Matthew
ABSTRACT: We investigated the narratives of enablers and barriers to entry into law communicated through 650 UK tweets posted under the twitter hashtag #mypathtolaw in 2018. Law students, solicitors, barristers and legal academics used this hashtag for sharing their personal paths to a legal career. We use Ricoeur's theory of dialogues between the archaeology (past) and the teleology (future) of the self. This has previously been applied to legal ethics, but never before to understanding access to the legal profession. Our findings show that tweeters had a strong narrative of agency and ability to succeed against adversity – perhaps underplaying structural barriers. Notable through its absence is the reference to structural barriers, such as class, school, and university type and the converse individual narratives of perseverance. We find that poor or discouraging careers advice had been a significant barrier. We conclude with recommendations for schools, universities and the legal profession around diversifying the narratives used to showcase legal careers and suggest that universities engaging in training for careers advisors may further widen participation.